Respuestas
Respuesta dada por:
4
Resolvemos.
3x - (- 2) - x = 2(4x - 6) + x
3x + 2 - x = 8x - 12 + x
3x - x + 2 = 8x + x - 12
2x + 2 = 9x - 12
2 + 12 = 9x - 2x
14 = 7x
14/7 = x
2 = x
3x - (- 2) - x = 2(4x - 6) + x
3x + 2 - x = 8x - 12 + x
3x - x + 2 = 8x + x - 12
2x + 2 = 9x - 12
2 + 12 = 9x - 2x
14 = 7x
14/7 = x
2 = x
Respuesta dada por:
5
3x- (-2) - x = 2 (4x - 6) +
3x +2 -x = 8x -12 +x
2x+ 2 = 9x -2x
14= 7x
14/7 = x
2=x
3x +2 -x = 8x -12 +x
2x+ 2 = 9x -2x
14= 7x
14/7 = x
2=x
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años